Developing strategies for creating an environmental focus in a school: narrating the change process - Hope, Megan Samantha (Rhodes University, Faculty of Education, Department of Education, 2005)
Effective environmental education goes beyond raising environmental awareness and developing positive environmental values, to the encouragement of personal responsibility and action in response to contextual environmental issues in particular. The whole school approach has been advocated as the best approach to environmental education, based on the assumption that the values and attitudes espoused in the classroom need to be reflected in the day-to-day school practice. By practising what they teach, schools reinforce values with action. In contrast, inconsistencies between the formal and non-formal curriculum may lead young people to question the integrity of their teachers or condition them to accept such inconsistencies as cultural and social norms, which in turn may lead to apathy about the environment. Adjustments to the ethos of a school to foreground the environment, both within the curriculum , the management of the school and the behaviour of teachers, pupils and support staff, is not a straightforward undertaking. Institutional factors influence the change process in schools and each school presents a unique context. It is, therefore, difficult to develop a general strategy for the evolution of an environmental ethos. This case study narrates an attempt to implement a change towards an improved environmental focus in a school, and focuses on developing an understanding of how available resources can assist this process while engaging with complexity of change.
Keywords: Environmental education; Educational change; School environment